The Jesus conspiracy an investigative reporter's look at an extraordinary life and death - Thomas, Gordon (Grand Rapids, MI Baker, 1997)
Includes bibliiographical references.
Originally published: The trial.-- London, UK : Bantam Press, 1987
Keywords: Jesus Christ -- trial; Jesus Christ -- passion